A new fully integrated X-ray irradiator system for dosimetric research. (June 2016) - Richter, D.; Mittelstraß, D.; Kreutzer, S.; Pintaske, R.; Dornich, K.; Fuchs, M.
Abstract: A fully housed X-ray irradiator was developed for use within lexsyg or Magnettech desktop equipment. The importance of hardening of the low energy photon radiation is discussed, its performance and feasibility is empirically shown and sustained by basic numerical simulations. Results of the latter for various materials are given for different X-ray source settings in order to provide estimates on the required setup for the irradiation of different geometries and materials. A Si-photodiode provides real-time monitoring of the X-ray-irradiator designed for use in dosimetric dating and other dosimetric application where irradiation of small samples or dosemeters is required. Highlights: Bench top X-ray irradiator provides variable dose-rates. Simulation of low energy photon irradiation and hardening of X-ray. Al-hardening for the irradiation of H2 O, BeO, Al2 O3, quartz, feldspars and zircon. Dosimetric dating equipment for luminescence and ESR.